Availability of highly sensitive troponin assays and acute coronary syndrome care: insights from the SNAPSHOT registry. Issue 1 (19th January 2015) - Cullen, Louise; French, John K; Briffa, Tom G; Redfern, Julie; Hammett, Christopher J K; Brieger, David B; Parsonage, William A; Lefkovits, Jeffrey; Ellis, Chris; Astley, Carolyn; Howell, Tegwen Eleanor; Elliott, John M; et al.
Abstract: Objectives: To examine differences in care and inhospital course of patients with possible acute coronary syndrome (ACS) in Australia and New Zealand based on whether a highly sensitive (hs) troponin assay was used at the hospital to which they presented. Design, setting and patients: A snapshot study of consecutive patients presenting to hospitals in Australia and New Zealand from 14 to 27 May 2012 with possible ACS. Main outcome measures: Rates of major adverse cardiac events (inhospital death, new or recurrent myocardial infarction, stroke, cardiac arrest or worsening heart failure); association between assay type and outcome (via propensity score matching and a generalised estimating equation [GEE]; averages of the predicted outcomes among patients who were treated with and without the availability of an hs assay (via inverse probability‐weighting [IPW] with regression‐adjusted estimators). Results: 4371 patients with possible ACS were admitted to 283 hospitals. Over half of the hospitals (156 [55%]) reported using the hs assay and most patients (2624 [60%]) had hs tests ( P = 0.004). Use of the hs assay was independent of hospital coronary revascularisation capability. Patients tested with the hs assay had more non‐invasive investigations (exercise tests, stress echocardiography, stress nuclear scans, and computed tomography coronary angiography) than those tested with the sensitive assay. However, there were no differences between the groups in rates of angiography or revascularisation. All adjusted analyses showed a consistently lower rate of inhospital events, including recurrent heart failure in patients for whom the hs assay was used (GEE odds ratio, 0.75; 95% CI, 0.60–0.94; P = 0.014); IPW analysis showed a 2.3% absolute reduction in these events with the use of the hs assay ( P = 0.018). Conclusion: Use of hs troponin testing of patients hospitalised with possible ACS was associated with an increased rate of non‐invasive cardiac investigations and fewer inhospital adverse events.